MATERNALISM, THE HIJAB, AND CITIZENSHIP: A CRITIQUE OF GENDER POLITICS PRACTICES IN INDONESIA - Yenny Juliana; Nikmatullah; Dahlia Hidayati (PT. Jurnal Center Indonesia Publisher, 2026)
This article examines political practices concerning gender issues in Indonesia by highlighting the roles of maternalism (ibuisme) and the hijab as symbolic political instruments. Maternalism positions women within the social construction of nurturing “mothers of the nation,” while the hijab functions as a symbol of religiosity and cultural identity used to strengthen electoral legitimacy. Although these symbols may provide women with access and acceptance in political spaces, they often limit the meaning of women’s participation by emphasizing symbolic representation rather than substantive capability and political ideas. This analysis employs a qualitative approach based on a literature review of academic studies on political representation, identity politics, patriarchy, and citizenship. The findings indicate that maternalism and the hijab reflect the persistent dominance of patriarchal culture in Indonesian politics, resulting in gender-biased forms of female citizenship. Therefore, critical awareness and deeper reflection are needed to ensure that women’s representation in politics does not remain merely symbolic but instead fosters substantive participation for a more inclusive democracy.